Fine-Tuning Cold Stress Response Through Regulated Cellular Abundance and Mechanistic Actions of Transcription Factors - Abdullah, Siti Nor Akmar; Azzeme, Azzreena Mohamad; Yousefi, Kobra (Frontiers in Plant Science, 2022)
Cold stress infliction can result in disastrous effects on the productivity and survival of plants. Cold stress response in plants requires crosstalk between multiple signaling pathways in particular the cold, heat and reactive oxygen species signaling network. Transcription factors (TFs) such as the CBF, MYB, bHLH and WRKY family of TFs are key players in the regulation of cold stress response at the molecular level. This review discusses some of the latest understanding on the regulation of expression and the mechanistic actions of plant TFs to address cold stress. It was shown that the plant response consists of early response, late response and memory reprogramming for long term protection against cold stress. The regulatory network can be differentiated into CBF-dependent and independent pathways involving different sets of TFs. Post-transcriptional regulation by miRNAs, control during ribosomal translation process and post-translational regulation involving 26S proteosomic degradation, affecting the cellular abundance of key regulatory TFs are important aspect of the regulation for cold acclimation. Fine-tuning of the regulation by TFs for adjusting to the cold stress condition involving the dynamic action of protein kinases, membrane ion channels, adapters, and modifiers is emphasized in this review.